A Scientometric Review of Social Media in Shaping Public Policy: Patterns, Themes, and Future Directions - Riski; Nurmandi, Achmad; Younus, Muhammad; Suardi, Wahdania (Universitas Muhammadiyah Malang, 2025)
This research examines the characteristics of social media trends and their relationship with public policy, using the Scopus database from 2014 to 2024 with the CiteSpace application. The database was searched from 2014 to 2024 using the CiteSpace application. Social media has become a significant platform for policy discourse, facilitating two-way communication between government and society and influencing agenda setting and public participation. Through scientometric data analysis of relevant academic publications, this study examines research trends, cross-disciplinary collaborations, and important themes emerging in the literature. Its findings indicate a significant surge in scholarly attention to this topic over the past decade, with a particular focus on transparency, participation, sentiment analysis, and the role of social media as a catalyst for policy change. In addition, the research revealed that the United States is a leading country in this area of research. It identifies gaps in research, including the absence of contextualized studies in developing countries and the need for more comprehensive investigations into the ethical implications, regulatory aspects, and long-term impact of social media on public policy processes. The study concludes that social media has the potential to be a transformational tool in public policy formation, provided it is managed with effective and ethical strategies